Kırmızı - Yıldıran, Ayşe (İstanbul Kültür Üniversitesi Yayınları, 2007)
Renksizlikten sonra ilk adlandırılan renk olan kırmızı, ateşin ve kanın rengi olarak ortaya çıkar. Yaşam, sağlık ve mutluluğun evrensel simgesi, güçlü ve çekici özellikleriyle güzellik, cinsellik, evlilik, doğum gibi kavramlarla da bütünleştirilir. Yüksek statülerin ayrıcalığı erguvan, kırmız kırmızısı, zincifre gibi renk tarihinin önemli ve değerli tonları kutsalın, büyük gizlerin, ölümsüzlüğün anlatımında da kullanılmıştır. Olumsuzluk kutbunda ise nefret, savaş, şeytan ve cehennemi temsil etmektedir.

Being the first denomination after unchromatic colors, red appears as the color of blood and fire. An universal symbol for life, healt and happiness, it is also associated with the concepts of beauty, sexuality, marriage, birth according to its powerfull and attractive features. Symbol of the prestige and high status, the important and valuable nuances of the history of color like purple, kermes and red cinnabar are used for the expression of the sacred, the Great Work, the immortality. It represents hatred, war, devil and hell as for the negative significances.
Keywords: Ateş; Kan; Dinamik; Yaşam; Statü; Fire; Blood; Dynamic; Life; Status